2023
DOI: 10.1021/acsagscitech.3c00104
|View full text |Cite
|
Sign up to set email alerts
|

Tebuconazole-Loaded Mesoporous Silica Nanoparticles Encapsulated with Chitosan and Their Application in Wheat Growth

Abstract: Controlled-release pesticide formulation exhibiting low phytotoxicity and long-term effectiveness is highly promising. In this work, a novel pH stimuli-responsive pesticide delivery system was established by combining spray drying with ion crosslinking to coat chitosan onto tebuconazole-loaded mesoporous silica nanoparticles (Teb@MSNs@CS). The results demonstrated that the loading capacity of Teb@MSNs@CS for tebuconazole (Teb) was approximately 25.80%. The chitosan attached on the mesoporous silica nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Currently, mesoporous silica nanoparticles (MSNs) as nanocarriers have been commonly employed in several fields, such as molecular loading, including nucleation, proteins, due to their surface modifiability, large surface area, large pore volumes, and stability. , Generally, the bare MSNs cause premature release of pesticides due to a large number of exposed pores, which greatly reduces the pesticide delivery efficiency . To overcome this drawback, the development of MSNs based on encapsulation strategies might prevent the premature release of active ingredient pesticides in MSNs . It has shown that chitosan, a natural polymer with good biodegradable and environmentally friendly characteristics, can be used as a gatekeeper for encapsulating MSNs. , Specifically, the active pesticide ingredient is first loaded into the pores of MSNs, and then encapsulants (e.g., chitosan) are used to seal the pores of MSNs to improve the stability and controlled release of the active pesticide ingredient …”
Section: Introductionmentioning
confidence: 99%
“…Currently, mesoporous silica nanoparticles (MSNs) as nanocarriers have been commonly employed in several fields, such as molecular loading, including nucleation, proteins, due to their surface modifiability, large surface area, large pore volumes, and stability. , Generally, the bare MSNs cause premature release of pesticides due to a large number of exposed pores, which greatly reduces the pesticide delivery efficiency . To overcome this drawback, the development of MSNs based on encapsulation strategies might prevent the premature release of active ingredient pesticides in MSNs . It has shown that chitosan, a natural polymer with good biodegradable and environmentally friendly characteristics, can be used as a gatekeeper for encapsulating MSNs. , Specifically, the active pesticide ingredient is first loaded into the pores of MSNs, and then encapsulants (e.g., chitosan) are used to seal the pores of MSNs to improve the stability and controlled release of the active pesticide ingredient …”
Section: Introductionmentioning
confidence: 99%